Can an integrated intervention package including peer support increase the proportion of health facility births? A cluster randomised controlled trial in Northern Uganda - Grace Ndeezi; Julius N Wandabwa; Thorkild Tylleskär; David Mukunya; James K Tumwine; Victoria Nankabirwa; Beatrice Odongkara; Agnes A Arach; Vicentina Achora; Paul Waako; Levi Mugenyi; Mohammad Boy Sebit (BMJ Open, 2024)
Objective To assess the effect of an integrated intervention package compared with routine government health services on the frequency of health facility births.Setting Three subcounties of Lira district in Northern Uganda.Design A cluster randomised controlled trial where a total of 30 clusters were randomised in a ratio of 1:1 to intervention or standard of care.Participants Pregnant women at ≥28 weeks of gestation.Interventions Participants in the intervention arm received an integrated intervention package of peer support, mobile phone messaging and birthing kits during pregnancy while those in the control arm received routine government health services (‘standard of care’).Primary and secondary outcome measures The primary outcome was the proportion of women giving birth at a health facility in the intervention arm compared with the control arm. Secondary outcomes were perinatal and neonatal deaths.Results In 2018–2019, 995 pregnant women were included in 15 intervention clusters and 882 in 15 control clusters. The primary outcome was ascertained for all except one participant who died before childbirth. In the intervention arm, 754/994 participants (76%) gave birth at a health facility compared with 500/882 (57%) in the control arm. Participants in the intervention arm were 35% more likely to give birth at a health facility compared with participants in the control arm, (risk ratio 1.35 (95% CI 1.20 to 1.51)) and (risk difference 0.20 (95% CI 0.13 to 0.27)). Adjusting for baseline differences generated similar results. There was no difference in secondary outcomes (perinatal or neonatal mortality or number of postnatal visits) between arms.Conclusion The intervention was successful in increasing the proportion of facility-based births but did not reduce perinatal or neonatal mortality.Trial registration number NCT02605369